Implementing Whole Brain Teaching Within A Pre-Service Teachers’ Introductory Programming Instruction: An Action Research Study - Fatimah Yetunde Akinrinola; Nofiu Oriyomi Iposu (Scientia Publica Media, 2025)
This study investigated the implementation of whole brain teaching within a constructivist teaching strategy in pre-service teachers’ programming education, towards enhancing their knowledge of procedural programming. From a qualitative paradigm lens, hermeneutic phenomenology guided the inquiry. The research strategy involves two action research cycles involving fifty-eight pre-service teachers purposively sampled over two academic sessions. The Whole Brain instructional plan was designed to facilitate the programming instruction. Data were collected through surveys, interviews, and classroom observations. The findings generated two themes: programming intervention promoted student engagement and pre-service teachers’ teaching strategies through self-confidence in problem-solving and self-regulation of learning. These results contributed to the literature on pedagogical innovations in the teaching of programming and provided recommendations for enhancing pre-service teachers’ programming learning with a focus on holistic brain development through the implementation of the whole-brain programming walk-around and instructional plan for programming lessons. For transparency in research, it is necessary to state that even though the data for this study were collected in 2016 and 2017, the data are still significant within the context of programming education. The findings of this study support current literature on constructivist learning and also address gaps in the implementation of whole-brain learning for programming teaching. The findings of this study cannot be generalized due to the nature of action research studies, but can be replicated in another context. Further exploration with larger sample sizes and diverse contexts could bolster the robustness and generalizability of these findings.